Association of subsequent shock after conversion to shockable rhythm with outcomes stratified by the type of initial non-shockable rhythm in children with out-of-hospital cardiac arrest. (24th May 2021) - Goto, Y; Funada, A; Maeda, T; Goto, Y
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Japan Society for the Promotion of Science (Grant-in-Aid for Scientific Research) Background/Introduction: The rhythm conversion from initial non-shockable to shockable rhythm during cardiopulmonary resuscitation (CPR) by emergency medical services (EMS) providers may be associated with neurologically intact survival after out-of-hospital cardiac arrest (OHCA) in children with an initial non-shockable rhythm. However, the prognostic significance of rhythm conversion stratified by the type of initial non-shockable rhythm is still unclear. Purpose: We aimed to investigate the association of subsequent shock after rhythm conversion to shockable rhythm with neurologically intact survival and shock delivery time (time from EMS-initiated CPR to first shock delivery) by the type of initial non-shockable rhythm in children with OHCA. Methods: We analysed the records of 19, 095 children (age <18 years) with OHCA treated by EMS providers. Data were obtained from a prospectively recorded Japanese nationwide Utstein-style database for a 13-year period (2005–2017). The primary outcome measure was 1-month neurologically intact survival, defined as cerebral performance category score of 1 to 2. Patients were divided into the initial pulseless electrical activity (PEA) (n = 3, 326 [17.4%]) and initial asystole (n = 15, 769 [82.6%]) groups. Results: The proportion of patients who received subsequent shock after conversion to shockable rhythm was significantly higher in the initial PEA than in the initial asystole groups (3.3% [109/3, 326] vs. 1.4% [227/15, 769], p < 0.0001). The shock delivery time was significantly shorter in the initial PEA than in the initial asystole groups (median [IQR], 8 min [5 min – 12 min] vs. 10 min [6 min – 16 min], p < 0.01). Among the initial PEA patients, there was no significant difference between subsequently shocked (10.0% [11/109]) and subsequently non-shocked patients (6.0% [192/3, 217], p = 0.10) regarding the rate of 1-month neurologically intact survival. However, after adjusting for 9 pre-hospital variables, subsequent shock with a delivery time of <10 min was associated with increased odds of neurologically intact survival compared with no shock delivery (adjusted odds ratio [OR], 2.45; 95% confidence interval [CI], 1.16–5.16], p = 0.018). Among the initial asystole patients, the rate of 1-month neurologically intact survival was significantly higher in the subsequently shocked (4.4% [10/227]) than in the subsequently non-shocked (0.7% [106/15, 542], p < 0.0001). A multivariate logistic regression model showed that subsequent shock with a delivery time of <10 min was associated with increased odds of neurologically intact survival compared with no shock delivery (adjusted OR, 9.77 [95% CI, 4.2–22.5], p < 0.0001). Conclusions: In children with OHCA with an initial non-shockable rhythm, subsequent shock after conversion to shockable rhythm during CPR was associated with increased odds of 1-month neurologically intact survival only when shock was delivered <10 min from EMS-initiated CPR regardless of the type of initial rhythm.